Devitrification-induced an Ultrahigh Strength Al-based Composite Maintaining Ductility. Issue 5 (May 2015) - Kan, Dong; Li, Xiaopeng; Yang, Baijun; Yang, Hongwang; Wang, Jianqiang
Abstract : A new Al-based composite consisting of submicron-sized α-Al matrix embedded with precipitated intermetallic phases was developed by controlling the devitrification process of an Al–Ni–Y–Co–La amorphous alloy. Such a homogeneous composite structure presented an ultrahigh strength of about 1.34 GPa and a large compressive plastic strain up to 22%. The unique mechanical properties during compression are mainly attributed to the dislocation slip deformation of ductile α-Al matrix and the shear-induced refinement of strengthening intermetallic phases.